2017
DOI: 10.1111/jocn.13986
|View full text |Cite
|
Sign up to set email alerts
|

There is more to perinatal mental health care than depression: Public health nurses reported engagement and competence in perinatal mental health care

Abstract: Without knowledge and skill among nurses in all aspects of perinatal mental health, women with significant mental health needs may be left to cope alone and lack the necessary prompt evidence-based interventions and supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
1
33
0
1
Order By: Relevance
“…Education and training have been shown to be effective in developing healthcare professionals’ confidence and competence to respond to women's perinatal mental health care needs (Jones et al, ; Morrell et al, ). Higgins, Downes, et al () found that PHNs who had received perinatal mental health specific education had statistically significant higher confidence and skills levels in comparison to those without perinatal mental health education. In relation to referral, PHNs primarily directed women to their GP and only 22% of PHNs referred to community mental health nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education and training have been shown to be effective in developing healthcare professionals’ confidence and competence to respond to women's perinatal mental health care needs (Jones et al, ; Morrell et al, ). Higgins, Downes, et al () found that PHNs who had received perinatal mental health specific education had statistically significant higher confidence and skills levels in comparison to those without perinatal mental health education. In relation to referral, PHNs primarily directed women to their GP and only 22% of PHNs referred to community mental health nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Limited international research has explored PHNs perinatal mental health education and training needs (Noonan, Galvin, et al, 2017b). In Ireland, Higgins, Downes, Carroll, Gill, and Monahan (2017b) concluded that PHNs lack knowledge and skills to provide comprehensive perinatal mental health care. Jomeen, Martin, and Jarrett (2018b) suggest that a complexity of factors may influence healthcare professionals' behaviours including negative attitudes towards women with mental health concerns and inaccurate illness perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that this was related to the variations in perceptions of the structure, function and purpose of LVs and the limited time allocated to intervention delivery in training programmes. Qualitative surveys of health visitors/public health nurses have highlighted the need for more detailed and relevant training, particularly with regard to the recognition and treatment of a broad range of MHPs (not just depression) (Alexandrou, Sakellari, Kourakos, & Sapountzi‐Krepia, ; Ashford, Ayers, & Olander, ; Cummings & Whittaker, ; Higgins et al, ; Jomeen, Glover, Jones, Garg, & Marshall, ).…”
Section: Discussionmentioning
confidence: 99%
“…These are often comorbid with each other (Biaggi, Conroy, Pawlby, & Pariante, ) or overlap with more complex or severe disorders (Vigod, Brown, Wilson, & Howard, ). Although the majority of women experience anxiety or depression, any clinician responsible for their care has to be aware of potential comorbidities, a diverse range of mental illnesses and the increased vulnerability of women to rapid deterioration in mental state or sudden onset of serious symptoms (Brummelte & Galea, ; Higgins, Downes, Carroll, Gill, & Monahan, ; NICE, ).…”
Section: Introductionmentioning
confidence: 99%
“…The participants of the current study also report the need for education and training. In the same way, (Higgins, Downes, Carroll, Gill, & Monahan, 2018) suggest that future education programmes need to move beyond postnatal depression and address the range of mental health problems that may impact women in the perinatal period.…”
Section: Need Of Educ Ati On and Tr Ainingmentioning
confidence: 99%